Multifocal lichen sclerosus. Case report - Hadas, Ewa; Żerdzińska, Aleksandra A.; Norek, Natalia; Chlasta, Edyta; Adamusińska, Anna (Dermatology Review/Przegląd Dermatologiczny, 2015)
Introduction. Lichen sclerosus (LS) is a chronic, inflammatory dermatosis of unknown etiology affecting skin and mucous membranes. It was first described in 1887 by Darier. Lichen sclerosus usually begins as a single or multiple plaques (rarely as lichenoid papules) gradually transforming into porcelain-white atrophic lesions. Depending on localization, it may manifest with itching, pain or a burning sensation and often may cause sexual dysfunction. Objective. Presentation of an LS case that posed diagnostic difficulties. Case report. We present a patient with clinical diagnosis of lichen planus hypertrophicus on the skin of forearms and hands which demonstrated histopathological features of LS. Additionally, the presence of LS lesions was found on the skin of the eyelid and penis. Conclusions . Our case seems to be interesting because of the differences between clinical and histopathological findings and multiple localization of lesions.